Newly produced T and B lymphocytes and T-cell receptor repertoire diversity are reduced in peripheral blood of fingolimod-treated multiple sclerosis patients. (May 2015) - Chiarini, M; Sottini, A; Bertoli, D; Serana, F; Caimi, L; Rasia, S; Capra, R; Imberti, L
Background: Fingolimod inhibits lymphocyte egress from lymphoid tissues, thus altering the composition of the peripheral lymphocyte pool of multiple sclerosis patients. Objective: The objective of this paper is to evaluate whether fingolimod determines a decrease of newly produced T- and B-lymphocytes in the blood and a reduction in the T-cell receptor repertoire diversity that may affect immune surveillance. Methods: Blood samples were obtained from multiple sclerosis patients before fingolimod therapy initiation and then after six and 12 months. Newly produced T and B lymphocytes were measured by quantifying T-cell receptor excision circles and K-deleting recombination excision circles by real-time PCR, while recent thymic emigrants, naive CD8 + lymphocytes, immature and naive B cells were determined by immune phenotyping. T-cell receptor repertoire was analyzed by complementarity determining region 3 spectratyping. Results: Newly produced T and B lymphocytes were significantly reduced in peripheral blood of fingolimod-treated patients. The decrease was particularly evident in the T-cell compartment. T-cell repertoire restrictions, already present before therapy, significantly increased after 12 months of treatment. Conclusions: These results do not have direct clinical implications but they may be useful for further understanding the mode of action of this immunotherapy for multiple sclerosis patients.